Optimisation of Extraction Process of Polysaccharides from Artemisia selengensis Turcz Stems and Analysis of Its Antioxidant and α-Glucosidase Inhibitory Activities - Jianchang CAO; Ruotong LI; Fen ZENG; Wei ZOU; Shuhan WANG; Lu ZHANG; Qiao DING (Shipin gongye ke-ji)
This paper aimed to optimise the extraction process of polysaccharides from amaranth stalks and evaluate their in vitro antioxidant and hypoglycaemic activities. The hot-water extraction process of polysaccharide from Artemisia selengensis Turcz stem (ASTS) was conducted by combining single factor experiment and Box-Benhnken response surface methodology with ASTS as the raw material. The crude polysaccharide was deproteinized to obtain refined ASTS polysaccharide (ASTS-P). The antioxidant activity of ASTS-P in vitro was measured with the scavenging rate of DPPH and ABTS+ free radicals and the total reducing power as the indicators. Its hypoglycemic activity in vitro was determined with its α-glucosidase inhibitory activity as the indicator. The optimum hot-water extraction process of crude polysaccharide from ASTS was found to be: extraction temperature 95 ℃, extraction time 3 h, extraction cycles 3 and solid-liquid ratio of 1:30 g/mL and the yield of the crude polysaccharide under these conditions was 20.92%±0.63%. The half-clearance rate (IC50) of DPPH and ABTS+ free radicals of ASTS-P was 0.447 and 0.214 mg/mL, respectively. The total reducing power of ASTS-P was 1.02 when the concentration of ASTS-P was 4 mg/mL. The IC50 of ASTS-P against α-glucosidase was 9.027 mg/mL. These results suggested that ASTS-P had good antioxidant activity and certain hypoglycemic activity in vitro. This work may serve as a reference point for the development and usage of polysaccharide from ASTS.